Abnormal Properties of Low‐Dimensional Confined Water (Small 31/2021). Issue 31 (6th August 2021) - Wang, Dianyu; Tian, Ye; Jiang, Lei
Abstract : Low‐Dimensional Confined Water In article number 2100788, Dianyu Wang, Ye Tian, and Lei Jiang summarize the physical properties of low‐dimensional confined water through several common forms ranging from artificial to biological areas. The confinement size and surface properties affect the water behavior and destroy the tetrahedral hydrogen bond coordination mode which results in its intrinsic properties changing seriously. Reviewing confined water could help understand some abnormal biological phenomena, and guide the artificial designs.